(untitled) - Jones , Sally M. (Boston, 2007)
Principles of Taxation for Business and Investment Planning, by Sally Jones is a different approach to the study of taxation from the traditional tax return preparation approach. This book teaches students to recognize the role taxes play in business and investment decisions. In addition, the book presents the general role of taxation and its implications across all taxpaying entities before discussing the details relevant to specific entities. This approach allows students to really grasp the fundamental concepts that are the foundation for specific tax rules. The benefit is that the students will understand the framework of the tax system, even though specific tax rules and regulations change from year to year.
Keywords: Investments,Đầu tư; Taxation,Thuế; United States,Hoa Kỳ